Court libraries at the time of Francesco Maria II della Rovere: the reconstruction project of the Grande Galleria of Carlo Emanuele I of Savoy - Erika Guadagnin; Federico Cesareo (Bibliothecae.it)
After a brief introduction outlining the object of the research – the Grande Galleria, inaugurated in 1608 at the behest of Duke Carlo Emanuele I of Savoy – and a concise review of the most recent secondary literature on the subject, the contribution focuses on the sources useful for its reconstruction, which provide information about its physical and conceptual space. The reorganization of the Library in the 18th century, along with subsequent dispersions, led to the loss of traces of the bibliographic units once housed within the Grande Galleria. The digital environment and technological innovations may help reconstruct this complex and multifaceted artefact. The recreated space thus becomes not only a virtual environment but also a symbolic and conceptual context, paving the way for new studies and reflections.